Teaching Narrative Writing Through Pictures Series Technique - Nursyamsi. H Nursyamsi. H (Universitas Lancang Kuning, 2014)
This Classroom Action Research aimed to find out the students’ improvement in writing narrative text through picture series technique at the eleventh grade of students of SMA Pesantren Putri Yatama Mandiri, South Sulawesi. The design of this research consisted of two cycles. One cycle consisted of four meetings. It means that there were eight meetings in two cycles. The sample in this research consisted 30 students . The instrument are reading test and observation sheet. The result of the students’ reading test in cycle I and cycle II had improve in different scores. There was improvement by students’ writing narrative ability at the end action of cycle II, it was proved by the mean score of cycle I was 60.52 that improved to be 76.51 in cycle II while the standard criteria for the achievement of mastery learning (KKM) 70. They were higher than means score of diagnostic test namely 45.68. This research proved Picture series technique could improve the students‘ writing narrative ability